Behavioral psychology and analytic philosophy: a convenient Alliance for the XXI century - Montgomery Urday, William (2007)
The relations between science of behavior and philosophy of science usually are conflicting and confused. Today, in comtemporary behavioral science they come discussing the philosophical roots with which its contextualist approach is compatible of general way.